Presumed Nonalcoholic Fatty Liver Disease Among Medicare Beneficiaries With HIV, 2006–2016. (7th January 2020) - Paik, James M; Henry, Linda; Golabi, Pegah; Alqahtani, Saleh A; Trimble, Gregory; Younossi, Zobair M
Abstract: Background: Newer treatments for HIV and hepatitis C virus (HCV) have decreased mortality in HIV/HCV patients. Nonalcoholic fatty liver disease (NAFLD) has increased globally; therefore, the prevalence and mortality of NAFLD among HIV (+) patients was assessed. Methods: Using Medicare denominator, inpatient, and outpatient files (random 5% sample per year), serial cross-sectional analysis (2006 to 2016) was performed. Joinpoint trend analysis evaluated prevalence and mortality with average annual percent change (AAPC). HIV (+) patients and liver diseases (LDs) were identified using International Classification of Diseases 9/10 codes. NAFLD was presumed using diagnosis codes or codes for metabolic dysfunction and obesity in absence of other LDs. Liver-related HIV (+) indicated HIV (+) patients with LDs. Results: Among 28 675 887 Medicare beneficiaries, 47 062 were HIV (+) (mean [SD] age, 51.4 [11.3] years); 11 920 had liver diseases (6923 HCV, 2019 hepatitis B virus [HBV], 2472 presumed NAFLD, 278 alcoholic liver disease [ALD], and 1653 other LDs); 2882 HIV (+) patients died; 1260 had LDs. The prevalence and mortality for non-liver-related HIV (+) decreased (AAPC, –1.1% and –9.1%). Liver-related HIV (+) increased (AAPC, 1.7%; P = .007); mortality leveled off. Prevalence and mortality worsened for presumed NAFLD (AAPC, 9.7% and 10.0%) and improved for HBV and HCV (HBV: AAPC, –3.5% and –8.8%; HCV: AAPC, –0.7% and –4.9%). After adjustments, HCV (odds ratio [OR], 2.00; 95% confidence interval [CI], 1.24–172), HBV (OR, 2.40; 95% CI, 2.09–2.77), ALD (OR, 5.70; 95% CI, 4.34–7.48), and presumed NAFLD (OR, 1.46; 95% CI, 1.24–1.72) increased 1-year mortality. Conclusions: Among HIV (+) subjects, viral hepatitis remains the leading LD for increased 1-year mortality, but the prevalence and mortality with presumed NAFLD are increasing.